Emphasizing the Importance of Naproxen Prophylaxis May Decrease the Rate of Heterotopic Ossification After Hip Arthroscopy - Ameen Z. Khalil, M.S; Natalya E. McNamara, M.D; Joseph Featherall, M.D; Allan K. Metz, M.D; Daniel C. Lewis, M.D; Stephen K. Aoki, M.D (Elsevier, 2024)
Purpose: To investigate the incidence of heterotopic ossification (HO) in patients prescribed prophylactic nonsteroidal anti-inflammatory drugs (NSAIDs), both before and after the introduction of a standardized education protocol. Methods: A retrospective review was conducted using a database of hip arthroscopy patients treated by a single surgeon at an academic hospital from 2015 to 2023. The inclusion criteria were (1) primary hip arthroscopy for the treatment of femoroacetabular impingement, (2) completion of a 2-week course of prophylactic postoperative NSAIDs (500 mg of naproxen twice daily), and (3) availability of follow-up radiographs at the 6-month postoperative visit. The control cohort was merely prescribed the postoperative prophylactic NSAIDs, whereas the intervention cohort also received dedicated in-person education, emphasizing the importance of NSAID adherence. The presence of HO was determined through review of follow-up radiographs. Standard descriptive statistics were used to describe the findings. Results: Both the control and intervention groups consisted of 200 continuous hip arthroscopy patients, with the control group treated from 2015 to 2017 and the intervention group treated from 2020 to 2023. Within the control group, 10 cases of HO (5%) were detected. Within the intervention group, 2 cases of HO (1%) were found. The Pearson χ2 test with Yates continuity correction produced a value of 4.21, with a P value of .04. Conclusions: In this study, we found a significantly lower incidence rate of HO in patients who received standardized education on the importance of NSAID compliance versus those who did not. This finding suggests that patient education may play a contributory role in reducing the incidence of HO after hip arthroscopy. Level of Evidence: Level III, comparative cohort study.